A Switched-Capacitor-Based Quasi-H7 Inverter for Common-Mode Voltage Reduction - Thi-Thanh Nga Nguyen; Tan-Tai Tran; Minh-Duc Ngo; Seon-Ju Ahn (Energies)
This paper proposes a novel three-phase two-level DC-AC inverter with significantly reduced common-mode voltage. The proposed inverter combines a conventional three-phase H7 configuration with a voltage multiplier network, effectively doubling the DC-link voltage relative to the input. Compared to existing solutions, the topology achieves a remarkably low common-mode voltage, limited to only 16.6% of the DC-link voltage. Additionally, the voltage stress across the additional switches remains at half of the DC-link voltage. The paper details the operating principles, mathematical formulation, and circuit-level analysis of the proposed inverter. Simulation results are provided to validate its performance. Furthermore, a hardware prototype has been implemented using a DSP TMS320F28379D microcontroller manufactured by Texas Instruments, headquartered in Dallas, TX, USA in conjunction with an Altera Cyclone® IV EP4CE22F17C6N FPGA-based digital control platform manufactured by Intel Corporation, headquarters in Santa Clara, CA, USA. Experimental results are presented to confirm the effectiveness and feasibility of the proposed design.